Hubungan Sosial Warga Tua dengan Pasangan Data Mikro daripada Limbongan, Kelantan (Jurnal Pembangunan Sosial, 2010)
Nowadays more and more people can reach old age. When individuals reaching old age, issues of relationship with their spouses is particularly important to be discussed. This article aims at discussing the relationship between the elderly people with their spouses. Utilizing data from a face-to-face interview with 214 Malay residents in rural Kelantan aged 60 years and older, this study investigated patterns, harmonious relationship, intimacy, closeness, as well as understanding between them. Results revealed that, (a) more than half of the elderly felt that any important decision is a family decision; works outside the house are husbands’ responsibility whereas house chores are the responsibility of the wives; (b) they have a harmonious relationship, having a mutual understanding, caring and compromising, as well as no complict arises; (c) they have a deep intimacy between them; (d) 53.8 percent of the respondents said they have a very close relationship, while another 46.2 percent have an intimate relationship; and (e) not many elderly couples reported that they do not have an understanding. It can be concluded that as someone gets older, they will likely to have a more intimate relationship with their other half.